Cardiovascular and renal oxidative stress-mediated toxicities associated with bisphenol-A exposures are mitigated by Curcuma longa in rats - Temitayo Ajibade; Oluwaseun Esan; Isreal Osawere; Moses Adetona; Oluwasanmi Aina; Odunayo Azeez; Ayobami Deborah Obisesan; Ademola Adetokunbo Oyagbemi; Olufunke Eunice Ola-Davies; Temidayo Omobowale; Adebowale Saba; Adeolu Adedapo; et al. (Mashhad University of Medical Sciences, 2024)
Objective: Curcuma longa Rhizome (CLR), due to its potent antioxidant phytochemical constituents, was investigated for its effects on bisphenol A (BPA)-induced cardiovascular and renal damage.Materials and Methods: Sixty rats were randomly selected, and grouped as control, BPA (100 mg/ kg), BPA and CLR 100 mg/kg, BPA and CLR 200 mg/kg, CLR 100 mg/kg, and CLR 200 mg/kg for 21 days. Oxidative stress indices, antioxidant status, blood pressure parameters, genotoxicity, and immunohistochemistry were determined.Results: Rats exposed to the toxic effects of BPA had heightened blood pressure, lowered frequency of micronucleated polychromatic erythrocytes, and decreased activities of antioxidant enzymes compared with rats treated with CLR. Moreover, administration of CLR significantly (p<0.05) lowered malondialdehyde content and reduced the serum myeloperoxidase activity. Immunohistochemical evaluation revealed significantly (p<0.05) increased expressions of cardiac troponin and Caspase 3 in the BPA group compared with the CLR-treated groups.Conclusion: C. longa ameliorated cardiotoxic and nephrotoxic actions of bisphenol-A via mitigation of oxidative stress, hypertension, and genotoxicity.